RANCANG BANGUN SISTEM PENGENDALI JARAK JAUH MENGGUNAKAN FREKUENSI RADIO HC-12 BERBASIS ANDROID - Dinda Melati; Lisa Adriana siregar (Jurnal Simetri Rekayasa, 2021)
The development of electronic technology especially with regard to automatic control is increasing in line with the development of the science and the automation of this automatic control technology is applied to the different electronic devices used daily to further assist in human work, However many things the current remote control system still has a shortage of people having to use a cost report. such as a pulse or a packaged Internet data currently used using a gateway text or the Internet. For the time being, automatic designs in remote control systems that use modulation frequencies work on radio frequencies, 4.333 MHZ. Which enables it to turn on and off electronics that are commonly used in everyday life. Examples: fans, water pumps, and lights. This device activates the bluetooth using a smartphone which a frequency of hc-12 will read then be processed and received by arduino. With this deleted design, the prototype of the remote control system, made possible by artificial androids to shut down and activate the home smart electronic devices.